Pembinaan TK/TPA Di Masjid Nuru Sadda Desa Samaturue Kecamatan Tellulimpoe Kabupaten Sinjai - Suriyati suriyati; Fahrul Fahrul; Darwis Darwis; Burhanuddin Burhanuddin (Fakultas Ushuluddin dan Komunikasi Islam, 2023)
Community service is a very important thing to do, especially related to mentoring and coaching on how to write the Koran specifically for TK/TPA in Korong hamlet, Samaturue Village, Tellulimpoe District, Sinjai Regency, which is an embodiment of children's potential in the religious field both in terms of reading and memorize prayers as well as other short suras contained in the Qur'an. The purpose of this service is to observe how the model for mentoring TK/TPA students in Samaturue Village is also to measure the level of ability of TK/TPA students in reading and memorizing short surahs. There are several ways to do coaching in TK/TPA, namely by observation, this is done to see and get an overview of the implementation and development of TK/TPA, second, activity planning, preparation of teaching materials, third, activity implementation, and evaluation, then followed up from the results of the implementation The results of this coaching found that out of 25 TK/TPA students all showed good results both in terms of reading ability using the Iqro, Tartil, and Qiroati methods. The follow-up to the results of this coaching activity is the submission of TK/TPA learning books which will later be used by the supervisor and then the next implementer to carry out coaching. The next implementation of PKM requires continuous and consistent assistance and coaching as well as commitment.